Positive electrode slurry auxiliary agent, positive electrode slurry and preparation method of positive electrode slurry auxiliary agent
By using a combination of non-polymer organic acids containing acid groups and dispersants in the positive electrode material of lithium battery, a positive electrode slurry additive with high cracking resistance and low water absorption rate is formed, and the conductivity and energy density of the positive electrode material of lithium battery is solved. Improve the problem and improve the stability and performance of the electrode sheet.
Patent Information
- Application Number
- CN202411342094.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-27
AI Technical Summary
The prior art is difficult to simultaneously improve conductivity, rate performance and energy density in the positive electrode materials of lithium batteries, and there are difficulties in cracking and water absorption rate control during electrode preparation, which affects battery performance.
Nonpolymer organic acid containing acid groups is used as functional monomers, combining the dispersed functional monomer and synergistic agent to form a positive electrode slurry additive with high cracking resistance and low water absorption rate, through specific components The proportion and preparation method are used to regulate the pH and dispersion properties of the slurry, and improve the crack resistance and water absorption characteristics of the electrode sheet.
It significantly improves the crack resistance of the positive electrode sheet and reduces the water absorption rate, improves the cycle stability and energy density of the battery, and reduces the capacity loss and thermal runaway risk of the battery during the fast charging and discharging process.
Smart Images

Figure CN119208608A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a positive electrode slurry additive, a positive electrode slurry and a preparation method thereof. Background Art
[0002] The chemical formula of lithium iron phosphate is LiFePO4, which has an olivine crystal structure and belongs to the orthorhombic system. The space group is Pnmb or Pnma. Its crystal structure is composed of tetrahedral PO4 groups and octahedral FeO6 groups. + Ions are embedded in the gaps between tetrahedra and octahedra to form a stable crystal structure. Thanks to the strong PO covalent bond in the phosphate group, the olivine structure of lithium iron phosphate is very stable. It can stabilize oxygen atoms in the fully charged state to prevent them from being oxidized to generate oxygen and released, thereby improving the safety of the material. Therefore, as an excellent olivine structure positive electrode material, lithium iron phosphate has excellent cycle stability and material performance, and has become the most widely used lithium battery positive electrode material.
[0003] However, compared with lithium cobalt oxide and ternary materials, lithium iron phosphate has relatively poor conductivity, which makes it difficult to obtain high-rate charge and discharge efficiency. In addition, the density of lithium that can be inserted and removed in lithium iron phosphate materials is lower than that of common layered materials such as ternary and lithium cobalt oxide, resulting in its energy density disadvantage. In order to improve the conductivity, rate performance and energy density of lithium iron phosphate, the main methods currently used are carbon coating and material particle size nano-sizing. For the carbon coating method, its working principle is that carbon materials have good conductivity. When carbon is coated on the surface of lithium iron phosphate particles, a conductive carbon layer can be formed, which provides an effective path for the transmission of electrons between lithium iron phosphate particles. This significantly enhances the electronic conductivity of lithium iron phosphate materials, allowing the battery to transmit current faster during the charge and discharge process, thereby improving the performance of the battery; at the same time, the carbon coating layer can improve the diffusion performance of lithium ions, allowing lithium ions to be inserted and removed faster during the charge and discharge process, thereby improving the rate performance of the battery; in addition, although the carbon coating layer itself does not directly contribute to energy density, it improves conductivity and rate performance, allowing the battery to release under the same conditions. More electric energy indirectly increases the energy density of the battery; the working principle of material particle size nano-sizing is to reduce the particle size of lithium iron phosphate particles, increase the contact area between particles, thereby improving the transmission efficiency of electrons between particles. In addition, nano-sizing can also increase the specific surface area of the material, so that more active sites are exposed, which is beneficial to the transmission of electrons and the embedding / ejection of lithium ions. Since the diffusion capacity of lithium ions is inversely proportional to the square of the particle size, reducing the particle size can greatly increase the diffusion rate of lithium ions, which enables the battery to maintain a high capacity and efficiency during rapid charging and discharging, thereby improving the battery's rate performance; at the same time, nano-sizing technology can enable more lithium ions to participate in the charging and discharging process by improving the electrochemical activity and utilization rate of lithium iron phosphate materials, which directly improves the specific capacity and energy density of the battery.
[0004] In the prior art, in order to fully improve the performance of lithium iron phosphate materials, carbon coating and material particle size nano-sizing are often used in combination. However, while reducing the particle size of lithium iron phosphate improves the electrical performance, it will increase the difficulty of preparation. Smaller particle size means larger specific surface area, which will increase the difficulty of carbon coating, resulting in increased residual alkali and pH on the surface. Higher pH increases the water absorption rate of the manufactured pole piece and higher hot pressing short circuit rate and tunnel furnace energy consumption of the battery cell. In addition, the larger specific surface area also makes it difficult to infiltrate the active material during the homogenization process and the slurry has poor stability, which in turn causes coating cracking.
[0005] In addition, the introduction of dispersants can effectively improve the stability of the slurry and optimize the cracking of the coating. For example, the Chinese patent with the publication (announcement) number CN117659331A discloses a method for preparing a three-dimensional network anti-cracking dispersion material. The prepared dispersant has the advantages of excellent dispersion performance and outstanding anti-cracking effect, and can take into account both dispersion and anti-cracking functions; in addition, the Chinese patent with the publication (announcement) number CN117820599A discloses a method for preparing an ultraviolet light-cured flexible anti-cracking agent, which improves the cracking degree of the positive electrode plate slurry by ultraviolet light-cured flexible anti-cracking agent. However, the existing dispersants only focus on improving the stability of the slurry and optimizing the anti-cracking performance, and do not improve the water absorption rate of the pole piece.
[0006] In recent years, with the development of lithium battery positive electrode materials towards high capacity and nano-size, the cracking and water absorption rates in the electrode preparation process have become more difficult to control. If a positive electrode slurry additive and positive electrode sheet with high anti-cracking performance and low water absorption rate can be developed, it will have a significant driving effect on the development of lithium battery technology. Summary of the invention
[0007] The object of the present invention is to provide a positive electrode slurry additive, a positive electrode slurry and a preparation method thereof with high anti-cracking performance and low water absorption rate in view of the above-mentioned technical problems.
[0008] In view of this, the present invention provides a positive electrode slurry additive, comprising:
[0009] Component A, which is a functional monomer having the function of reducing the water absorption rate of the electrode, and the component A is a non-polymer organic acid containing an acidic group;
[0010] Component B, which is a functional monomer having a dispersing effect;
[0011] Component C, which is a synergist;
[0012] and, organic solvents;
[0013] Component A and component B form the positive electrode slurry additive under the action of synergist component C.
[0014] Furthermore, the acidic group is a carboxyl group.
[0015] Furthermore, the molecular weight of component A is less than 180.
[0016] Furthermore, the component A is selected from one or more of 2-oxopropionic acid, 2,3-dihydroxysuccinic acid, 1,2-ethanedicarboxylic acid, and 2-hydroxypropionic acid.
[0017] Furthermore, the component B is selected from one or more of polyoxyethylene lauryl ether, polyoxyethylene nonylphenyl ether, stearic acid monoglyceride, and monostearate sorbitan ester.
[0018] Furthermore, the component C is selected from one or more of sodium 2,3-dihydroxysuccinate, sodium 2-hydroxypropionate, polybutyl acrylate, and hydrogenated nitrile rubber.
[0019] Furthermore, the organic solvent is at least one of N-methylpyrrolidone, N,N-dimethylformamide and dimethyl sulfoxide.
[0020] Furthermore, the weight ratio of component A: component B: component C is (5-25): (10-20): (3-7).
[0021] A method for preparing a positive electrode slurry additive, the method is used to prepare the positive electrode slurry additive described above, the method comprising the steps of:
[0022] S1, adding component A, component B and an organic solvent into a preparation container according to a weight ratio, stirring to make the mixture uniform and then setting aside;
[0023] S2, introducing an inert gas into the container, and heating the container to a set temperature, adding component C according to a weight ratio after keeping the temperature at a constant temperature and pressure, stirring the reaction, removing from the pot, and cooling to obtain the positive electrode slurry additive.
[0024] A positive electrode slurry contains 0.01 to 3 wt % of the positive electrode slurry additive mentioned above.
[0025] The beneficial effects of the present invention are:
[0026] In the present invention, the functional monomer component A having the effect of reducing the water absorption rate of the electrode sheet and the functional monomer component B having the dispersing effect form the positive electrode slurry additive under the action of the synergist component C. When the positive electrode slurry additive is added to the positive electrode slurry, the crack resistance of the prepared positive electrode sheet can be significantly improved, while reducing the water absorption rate of the positive electrode sheet.
[0027] In addition, in the present invention, component A used is a non-polymer organic acid containing an acidic group, and the molecular weight of component A is relatively small. Compared with high molecular weight polymer acids, the low molecular weight non-polymer organic acid used in the present invention can effectively avoid the uneven dispersion caused by its own steric hindrance effect, which is beneficial to its combination with the water absorption active sites on the surface of lithium iron phosphate. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the surface state of the positive electrode sheet obtained in Example 1 of the present invention observed under a microscope. DETAILED DESCRIPTION
[0029] The technical solutions in this application will be described clearly below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of this application, rather than all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments in this application belong to the scope of protection of this application.
[0030] In the description of the present application, it should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. The techniques, methods and devices known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, the techniques, methods and devices should be considered as part of the authorization specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary and not as a limitation. Therefore, other examples of the exemplary embodiments may have different values.
[0031] It should be noted that, in the present application, the terms "comprise", "include" or any other variant thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises one..." does not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be noted that the scope of the method and device in the embodiment of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.
[0032] A positive electrode slurry additive, comprising:
[0033] Component A, which is a functional monomer having the function of reducing the water absorption rate of the electrode, and the component A is a non-polymer organic acid containing an acidic group;
[0034] Component B, which is a functional monomer having a dispersing effect;
[0035] Component C, which is a synergist;
[0036] and, organic solvents;
[0037] Component A and component B form the positive electrode slurry additive under the action of synergist component C.
[0038] It should be noted that the acidic groups mainly refer to chemical groups that can generate hydrogen ions after hydrolysis or ionization under specific conditions. The presence of these groups makes the compounds containing them show acidic characteristics in the solution.
[0039] As some examples of the present invention, the acidic group can be a carboxyl group (—COOH), which is one of the most common acidic groups and is widely present in organic acids, such as acetic acid, citric acid, etc. The carboxyl group can ionize hydrogen ions in aqueous solution, thereby showing acidity. In addition, the hydroxyl group in phenolic compounds also has a certain acidity and can ionize hydrogen ions in water, so the acidic group can also be a phenolic hydroxyl group (—OH, connected to the benzene ring); the sulfonyl group in sulfonic acid and its derivatives is a strong acidic group that can completely ionize hydrogen ions in water, so the acidic group can also be a sulfonyl group (—SO3H); although the acylamino group itself does not directly ionize hydrogen ions, under certain conditions, it can participate in the hydrolysis reaction and indirectly produce an acidic effect, so the acidic group can also be an acylamino group (—CONH2); in some cases, the thiophenol group also shows a certain acidity, so the acidic group can also be a thiophenol group (—SH, similar to the phenolic hydroxyl group but sulfur replaces oxygen).
[0040] However, through many tests and comparisons, it was found that when the non-polymer organic acid containing a carboxyl group is used as the positive electrode slurry additive described in the present invention, the water absorption rate of the obtained electrode sheet is significantly better than that of other acidic groups. Therefore, the present invention preferably uses a carboxyl group as the acidic group in component A.
[0041] Furthermore, the molecular weight of component A is less than 180, and preferably, the molecular weight of component A is less than 160.
[0042] As some examples of the present invention, the component A is selected from one or more of 2-oxopropionic acid, 2,3-dihydroxysuccinic acid, 1,2-ethanedicarboxylic acid, and 2-hydroxypropionic acid.
[0043] In the present invention, component A used is a non-polymer organic acid containing an acidic group, and the molecular weight of component A is relatively small, such as 2-oxopropionic acid, 2,3-dihydroxysuccinic acid, 1,2-ethanedicarboxylic acid, and 2-hydroxypropionic acid, whose molecular weights are 88, 150, 118, and 90, respectively. Compared with high molecular weight polymer acids, the low molecular weight non-polymer organic acid used in the present invention can effectively avoid the uneven dispersion caused by its own steric hindrance effect, which is beneficial to its combination with the water absorption active sites on the surface of lithium iron phosphate.
[0044] Preferably, the component A is 2-oxopropionic acid, which is a weakly acidic organic acid having both carbonyl and carboxyl functional groups in its molecule. In addition to the properties of carboxylic acid and ketone, it also has the properties of α-keto acid, is the simplest α-keto acid, and is a carbonyl acid. 2-Oxopropionic acid can simultaneously provide the properties of carboxylic acid and ketone, as well as the special properties of α-keto acid, which brings many aspects of performance improvement to lithium battery additives. For example, 2-oxopropionic acid has the properties of carboxylic acid and ketone. These functional groups can interact with other components in the electrolyte to form a more stable chemical structure, thereby improving the chemical stability of the electrolyte, reducing the battery performance degradation caused by electrolyte decomposition or deterioration, and extending the service life of the lithium battery; in addition, the properties of α-keto acid enable 2-oxopropionic acid to provide additional electron transfer pathways during battery charging and discharging, which helps the insertion and deintercalation of lithium ions, reduces the capacity loss of the battery during the cycle, and improves the cycle stability and service life of the battery; in addition, as an organic acid, 2-oxopropionic acid may, to a certain extent, inhibit the oxygen and hydrogen generated in the electrolyte during overcharging, reduce the internal pressure of the battery, reduce the risk of battery explosion or fire, and reduce the risk of thermal runaway of the battery under extreme conditions.
[0045] As some examples of the present invention, the component B is selected from one or more of lauryl polyoxyethylene ether, polyoxyethylene nonylphenyl ether, stearic acid monoglyceride, and monostearate sorbitan ester.
[0046] As some examples of the present invention, the component C is selected from one or more of sodium 2,3-dihydroxysuccinate, sodium 2-hydroxypropionate, polybutyl acrylate, and hydrogenated nitrile rubber.
[0047] As some examples of the present invention, the specific selection of the organic solvent is preferably to be able to dissolve the formulated amount of component A, component B and component C. Preferably, the organic solvent is at least one of N-methylpyrrolidone, N,N-dimethylformamide and dimethyl sulfoxide.
[0048] Preferably, the weight ratio of component A: component B: component C: organic solvent is (5-25): (10-20): (3-7): (48-82).
[0049] More preferably, the weight ratio of component A:component B:component C:organic solvent is (10-20):(13-16):(4-6):(60-80).
[0050] In addition, the present invention also provides a method for preparing a positive electrode slurry additive, the method is used to prepare the above-mentioned positive electrode slurry additive, the method comprises the steps of:
[0051] S1, adding component A, component B and an organic solvent into a preparation container according to a weight ratio, stirring to make the mixture uniform and then setting aside;
[0052] S2, introducing an inert gas into the container, and heating the container, and then adding component C according to the weight ratio after keeping it warm at a constant temperature and pressure, and then continuing to stir the reaction, taking it out of the pot, and cooling it down to obtain the positive electrode slurry additive.
[0053] As some embodiments of the present invention, the inert gas is selected from argon, nitrogen and the like.
[0054] Preferably, the method for preparing the positive electrode slurry additive comprises the steps of:
[0055] S1: Add a certain proportion of component A, component B and organic solvent into the double planetary mixer according to the weight ratio, and mix and disperse the solution evenly through the stirring and dispersing functions;
[0056] S2: Introduce argon into the mixer through a flow valve to maintain a set pressure in the mixer, and introduce heat transfer oil through the mixer jacket to maintain a set temperature in the mixer; maintain the mixture under constant temperature and pressure for 1 to 3 hours, then add component C according to the weight ratio, and then continue to react under the set temperature and pressure, stirring for 0.3 to 2 hours, then remove from the pot and cool down to obtain a finished positive electrode slurry additive that prevents cracking and reduces the water absorption rate of the positive electrode sheet; wherein the set pressure is 0.1 to 2 MPa, and the temperature is 60 to 100°C.
[0057] Furthermore, the present invention also provides a positive electrode slurry, wherein the positive electrode slurry contains 0.01 to 3 wt % of the positive electrode slurry additive.
[0058] Furthermore, the preparation process of the positive electrode slurry is as follows:
[0059] The positive electrode slurry additive is added to the pre-prepared positive electrode base slurry according to a weight ratio, and the positive electrode slurry is obtained after being stirred evenly.
[0060] As some examples of the present invention, the positive electrode base slurry includes 70 to 120 parts by weight of lithium iron phosphate, 0.5 to 3 parts by weight of a conductive agent, 0.5 to 4 parts by weight of a binder, and 40 to 100 parts by weight of an organic solvent I.
[0061] Furthermore, the conductive agent may be conductive carbon black; the binder may be a binder; and the organic solvent I may be N-methylpyrrolidone.
[0062] Furthermore, the positive electrode slurry can be used to prepare positive electrode sheets of various shapes and specifications. The preparation process of the positive electrode sheet is as follows: the positive electrode slurry is coated on aluminum foil in a certain thickness, such as 100um, 200um, 350um, and 500um, and dried at a temperature of 100-160°C for 0.2-3h to obtain the positive electrode sheet.
[0063] The applicant discovered through research that directly introducing carboxylic acid substances into the electrode slurry will affect the formation of hydrogen bonds between the binder PVDF and the positive electrode current collector while reducing the water absorption rate of the electrode sheet, thereby greatly causing a decrease in the peeling force of the electrode sheet and causing the electrode sheet to fall off and cause battery failure. This is why carboxylic acid substances have never been actually used as lithium battery additives on a large scale.
[0064] In the present invention, the applicant has found through further research that when the component A used is a non-polymer organic acid containing an acidic group and the molecular weight of component A is relatively small, compared with the high molecular weight polymer acid, the low molecular weight non-polymer organic acid used can effectively avoid the uneven dispersion caused by its own steric hindrance effect, which is beneficial to its combination with the water absorption active site on the surface of lithium iron phosphate; and when the acidic group is introduced, a synergist is added, and the organic weak acid and strong base salt corresponding to the synergist can regulate the hydrogen ion concentration of the slurry system. Specifically: by controlling the type selection and proportion of the non-polymer organic acid containing an acidic group and the synergist, the attack ability of hydrogen ions on the water absorption active site and PVDF in the slurry system can be effectively regulated, so that it can reduce the water absorption rate while ensuring the bonding strength between the electrode material and the current collector, and finally achieve the simultaneous improvement of the anti-cracking performance and the water absorption rate.
[0065] In addition, while component B containing polyether groups improves the dispersion of the slurry and prevents cracking, it will cause the flexibility of the electrode to deteriorate and it is easy to break during the coating and drying process. The synergist introduced in the present invention can effectively enhance the flexibility of the electrode, and further effectively prevent the cracking of the electrode during the baking process by regulating the types and proportions of component B and component C.
[0066] Furthermore, in the present invention, the non-polymer organic acid containing an acidic group can form a buffer system with the synergist component C to control the pH of the slurry within an appropriate range.
[0067] The positive electrode slurry additive and the positive electrode slurry of the present invention are illustrated by specific examples below:
[0068] Example 1
[0069] (1) 15 parts by mass of 2-oxopropionic acid, 15 parts by mass of lauryl polyoxyethylene ether and 70 parts by mass of N-methylpyrrolidone were added to a double planetary mixer, and the solution was evenly dispersed by stirring and dispersing functions;
[0070] (2) introducing argon gas into the mixer through a flow valve to maintain a pressure of 0.8 MPa in the mixer, introducing heat transfer oil through the mixer jacket to maintain a temperature of 80° C., stirring at a constant temperature and pressure for 2 h, then adding 5 parts by weight of sodium 2,3-dihydroxysuccinate, and then continuing to stir at the set temperature and pressure for 1 h before removing from the pot and cooling to obtain a positive electrode slurry additive;
[0071] (3) The positive electrode slurry additive obtained above is added to the prepared positive electrode base slurry (the formula of the positive electrode base slurry is lithium iron carbonate: conductive carbon black: polyvinylidene fluoride: N-methylpyrrolidone = 97:1.2:1.8:60) to obtain a positive electrode slurry, and the mass proportion of the positive electrode slurry additive in the positive electrode slurry is controlled to be 0.15%, and it is coated on a 13 μm thick aluminum foil with a thickness of 270 μm, and dried in an oven at a temperature of 130°C for 0.5 h to obtain a positive electrode sheet.
[0072] Example 2
[0073] (1) 10 parts by mass of 2,3-dihydroxysuccinic acid, 13 parts by mass of polyoxyethylene nonylphenyl ether and 60 parts by mass of N,N-dimethylformamide were added to a double planetary mixer, and the solution was dispersed uniformly by stirring and dispersing functions;
[0074] (2) introducing argon gas into the mixer through a flow valve to maintain a pressure of 0.1 MPa in the mixer, introducing heat transfer oil through the mixer jacket to maintain a temperature of 60° C., stirring at a constant temperature and pressure for 3 h, then adding 4 parts by weight of sodium 2-hydroxypropionate, and then continuing to stir at the set temperature and pressure for 2 h before removing from the pot and cooling to obtain a positive electrode slurry additive;
[0075] (3) Add the positive electrode slurry additive obtained above to the prepared positive electrode base slurry (the formula of the positive electrode base slurry is lithium iron carbonate: conductive carbon black: polyvinylidene fluoride: N-methylpyrrolidone = 97:1.2:1.8:60) to obtain a positive electrode slurry, and control the mass proportion of the positive electrode slurry additive in the positive electrode slurry to be 0.01%, and coat it on a 13 μm thick aluminum foil with a thickness of 150 μm, and dry it in an oven at a temperature of 100°C for 2 hours to obtain a positive electrode sheet.
[0076] Example 3
[0077] (1) 20 parts by mass of 1,2-ethanedicarboxylic acid, 16 parts by mass of stearic acid monoglyceride and 80 parts by mass of dimethyl sulfoxide were added into a double planetary mixer, and the solution was dispersed uniformly by stirring and dispersing functions;
[0078] (2) introducing argon gas into the mixer through a flow valve to maintain a pressure of 2 MPa in the mixer, introducing heat transfer oil through the mixer jacket to maintain a temperature of 100° C., stirring at constant temperature and pressure for 1 hour, then adding 6 parts by weight of hydrogenated nitrile rubber, and then continuing to stir at the set temperature and pressure for 0.3 hour, then removing from the pot and cooling to obtain a positive electrode slurry additive;
[0079] (3) Add the positive electrode slurry additive obtained above to the prepared positive electrode base slurry (the formula of the positive electrode base slurry is lithium iron carbonate: conductive carbon black: polyvinylidene fluoride: N-methylpyrrolidone = 97:1.2:1.8:60) to obtain a positive electrode slurry, and control the mass proportion of the positive electrode slurry additive in the positive electrode slurry to be 3%, and coat it on a 13 μm thick aluminum foil with a thickness of 350 μm, and dry it in an oven at a temperature of 160°C for 3 hours to obtain a positive electrode sheet.
[0080] Example 4
[0081] This embodiment is substantially the same as the embodiment 1, except that: 2-oxopropionic acid is 5 parts by mass, lauryl polyoxyethylene ether is 10 parts by mass, and sodium 2,3-dihydroxysuccinate is 3 parts by mass.
[0082] Example 5
[0083] This embodiment is substantially the same as the embodiment 1, except that: 2-oxopropionic acid is 25 parts by mass, lauryl polyoxyethylene ether is 20 parts by mass, and sodium 2,3-dihydroxysuccinate is 7 parts by mass.
[0084] Example 6
[0085] The only difference between this embodiment and embodiment 1 is that the mass proportion of the positive electrode slurry additive in the positive electrode slurry is controlled to be 5%.
[0086] Comparative Example 1
[0087] The difference between the present invention and the above-mentioned embodiment 1 is that in step (3), the positive electrode slurry without adding the positive electrode slurry additive in the above-mentioned embodiment 1 is coated and dried according to the same process as that in embodiment 1 to obtain a positive electrode sheet.
[0088] Comparative Example 2
[0089] The acidic compound -[CH(COOH)-CH(COOH)]-n with a molecular weight of 100,000 described in Example 1 of the Chinese patent publication number CN101685862A was used to replace the 2-oxopropionic acid in Example 1 of the present application.
[0090] Comparative Example 3
[0091] The only difference from Example 1 is that no sodium 2,3-dihydroxysuccinate is added.
[0092] Comparative Example 4
[0093] The only difference from Example 1 is that no lauryl polyoxyethylene ether is added.
[0094] Test Example 1
[0095] The positive electrode sheets prepared in the above embodiments and comparative examples were tested for cracking performance and water absorption rate. The test results are shown in Table 1 below. The water absorption rate test used the difference between the water content of the positive electrode sheet at 24h and 0h obtained by Karl Fischer water content tester, and the difference was used to characterize the water absorption rate. The cracking performance test was judged by observing the surface state of the electrode sheet under a microscope.
[0096] The positive electrode sheet obtained in Example 1 was placed under a microscope to observe its cracking condition. Figure 1 shown.
[0097] Table 1 Test results of cracking performance and water absorption rate of positive electrode
[0098]
[0099] By comparison, we can see that:
[0100] (1) The positive electrode slurry additive of the present invention can significantly improve the cracking of the positive electrode sheet during the baking process;
[0101] (2) The positive electrode slurry additive described in the present invention can significantly reduce the water absorption rate of the positive electrode sheet.
[0102] The embodiments of the present application are described above. In the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application is not limited to the above-mentioned specific implementation methods. The above-mentioned specific implementation methods are merely illustrative and not restrictive. Under the guidance of the present application, ordinary technicians in this field can also make many forms without departing from the purpose of the present application and the scope of protection of the claims, all of which are within the protection of the present application.
Claims
1. A positive electrode slurry additive, characterized in that: include: Component A, which is a functional monomer having the function of reducing the water absorption rate of the electrode, and the component A is a non-polymer organic acid containing an acidic group; Component B, which is a functional monomer having a dispersing effect; Component C, which is a synergist; and, organic solvents; Component A and component B form the positive electrode slurry additive under the action of synergist component C.
2. The positive electrode slurry additive according to claim 1, characterized in that: The acidic group is a carboxyl group.
3. The positive electrode slurry additive according to claim 1 or 2, characterized in that: The molecular weight of component A is less than 180.
4. The positive electrode slurry additive according to claim 3, characterized in that: The component A is selected from one or more of 2-oxopropionic acid, 2,3-dihydroxysuccinic acid, 1,2-ethanedicarboxylic acid, and 2-hydroxypropionic acid.
5. The positive electrode slurry additive according to claim 1, characterized in that: The component B is selected from one or more of polyoxyethylene lauryl ether, polyoxyethylene nonylphenyl ether, stearic acid monoglyceride, and monostearate sorbitan ester.
6. The positive electrode slurry additive according to claim 1, characterized in that: The component C is selected from one or more of sodium 2,3-dihydroxysuccinate, sodium 2-hydroxypropionate, polybutyl acrylate, and hydrogenated nitrile rubber.
7. The positive electrode slurry additive according to claim 1, characterized in that: The organic solvent is at least one of N-methylpyrrolidone, N,N-dimethylformamide and dimethyl sulfoxide.
8. The positive electrode slurry additive according to claim 1, characterized in that: The weight ratio of component A: component B: component C is (5-25): (10-20): (3-7).
9. A method for preparing a positive electrode slurry additive, characterized in that: The method is used to prepare the positive electrode slurry additive according to any one of claims 1 to 8, and the method comprises the steps of: S1, adding component A, component B and an organic solvent into a preparation container according to a weight ratio, stirring to make the mixture uniform and then setting aside; S2, introducing an inert gas into the container, and heating the container, and then adding component C according to a weight ratio after keeping the container warm at a constant temperature and pressure, stirring the reaction, and then removing the container from the pot and cooling the container to obtain the positive electrode slurry additive.
10. A positive electrode slurry, characterized in that: The positive electrode slurry contains 0.01 to 3 wt % of the positive electrode slurry additive according to any one of claims 1 to 8.
Citation Information
Patent Citations
Lithium ion battery positive electrode slurry, preparation method thereof and prepared pole piece and battery
CN101685862A
Preparation method of three-dimensional network anti-cracking dispersing material and preparation method of positive pole piece
CN117659331A
Preparation method of ultraviolet curing softening anti-cracking agent, positive electrode slurry and preparation method thereof, and preparation method of positive electrode plate
CN117820599A
